Struggling to Understand the Stock Market - Hall, Robert E (American Economic Review, 2001)
Economists are as perplexed as anyone by the behavior of the stock market. Figure 1 shows a broad measure of stock-market value in relation to GDP from 1947 through 2000. In addition to saw-tooth movements including the contraction in late 2000, the value of the stock market has large, low-frequency swings, moving upward from 1950 to 1965, then downward to 1982, and upward until early 2000. I entertain the hypothesis that these large movements are the result of rational (if not accurate) appraisal of the cash likely to be received by shareholders in the future. The hypothesis receives some support from work by financial economists showing that irrational markets create profit opportunities for active traders and that passive traders consistently earn higher returns. Most of my discussion will be complementary to the work of financial economists—I will look at the fundamentals underlying stock-market values. The lecture considers three potential contributors to the big movements shown in Figure 1: